Empowerment of Village Women Based on Local Wisdom in Efforts to Achieve Family Food Security (A Study on Women's Ex-Migrant Workers in Indonesia - Druju Village - Malang Regency) - Eny Yuniriyanti; Ririn Sudarwati; Bambang Nurdewanto (Jurnal Perempuan dan Anak, 2020)
Rural women are very dependent on the natural environment. However, in the majority of village resources that do not care about the role of women, increasingly increasing women's access and control of resources in the village and marginalized from the development process. Analysis of post-Indonesian Migrant Workers-Women (PMI-P) using the GIS (Geographic Information System) method and factor analysis in an effort to determine the empowerment program of Indonesian Migrant-Women Workers (PMI-P) in accordance with local wisdom. Women as housewives in addition to their role in helping husbands to find additional income for assistance are also responsible for managing the family economy. Those who survive with very affordable money can still eat well and survive. Acceptable women have an important role in efforts to increase family resilience. Based on the local wisdom of Druju Village, the researcher offers two business choices that make processed products made from batik and processed products made from corn. With the analysis of factors obtained by the results of the female respondents Druju Village prefers processing business products made from batik. Based on the empowerment capital determined by Druju Village, the strategy of empowering women workers is in accordance with the Aras Mezzo strategy, with the aim of empowering the establishment of a Joint Business Group (KUB) of processed products made from batik